2016
DOI: 10.1021/jacs.5b13080
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-Conjugated Rhenium Catalysts for Carbon Dioxide Reduction

Abstract: Condensation of fac-Re(5,6-diamino-1,10-phenanthroline)(CO)3Cl to o-quinone edge defects on graphitic carbon surfaces generates graphite-conjugated rhenium (GCC-Re) catalysts that are highly active for CO2 reduction to CO in acetonitrile electrolyte. X-ray photoelectron and X-ray absorption spectroscopies establish the formation of surface-bound Re centers with well-defined coordination environments. GCC-Re species on glassy carbon surfaces display catalytic currents greater than 50 mA cm(-2) with 96 ± 3% Fara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
191
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 35 publications
12
191
0
Order By: Relevance
“…However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts. [48,49] Among heterogeneous catalysts, N-G-supported SACs possess similar active centers to that of the molecular catalysts for NRR ( Figure 1b). Therefore, investigation on the catalytic activity of N-G supported SACs for NRR is of great importance.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts. [48,49] Among heterogeneous catalysts, N-G-supported SACs possess similar active centers to that of the molecular catalysts for NRR ( Figure 1b). Therefore, investigation on the catalytic activity of N-G supported SACs for NRR is of great importance.…”
Section: Resultsmentioning
confidence: 96%
“…For NRR, several molecular catalysts, such as Fe‐, Co‐ and Mo‐nitride complexes, have been prepared, where the MN x moieties serve as the active centers ( Figure a). However, molecular catalysts generally exhibit poorer durability and are less readily incorporated into electrolyzers in comparison with heterogeneous catalysts . Among heterogeneous catalysts, N–G‐supported SACs possess similar active centers to that of the molecular catalysts for NRR (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the methodo fi mmobilization, the heterogenized molecular catalystc an be removed from the electrode surfacea nd reused, whichi sn ecessary for energy-converting applications. Covalent attachment, [22][23][24][25] electropolymerization, [26][27][28][29][30] and adsorption/noncovalent attachment of metal complexes [31][32][33][34][35] are methods of heterogenizing molecular catalysts for energy-conversion applications and were reviewed elsewhere. [36][37][38]…”
Section: Molecular Electrocatalysts For Energy Conversionmentioning
confidence: 99%
“…We have shown that this functionalization method generates graphite-conjugated catalysts (GCCs) that display high activity for the ORR in alkaline aqueous media, and that the activity of these GCCs is sensitive to the structure of the molecular fragment incorporated. 45,48 Our initial synthetic studies of structure-activity correlations on GCCs identified carbon surfaces treated with aryl-pyridinium-substituted diamines, dubbed N + -GCCs, to be particularly active for the ORR (Scheme 1). 45 With well-defined catalytic sites and appreciable activity, N + -GCCs are an ideal platform for detailed experimental investigations of the kinetics of ORR catalysis.…”
Section: Introductionmentioning
confidence: 99%